2010
DOI: 10.1037/a0017606
|View full text |Cite
|
Sign up to set email alerts
|

Grasping beer mugs: On the dynamics of alignment effects induced by handled objects.

Abstract: We examined automatic spatial alignment effects evoked by handled objects. Using color as the relevant cue carried by an irrelevant handled object aligned or misaligned with the response hand, responses to color were faster when the handle aligned with the response hand. Alignment effects were observed only when the task was to make a reach and grasp response. No alignment effects occurred if the response involved a left-right key press. Alignment effects emerged over time, becoming more apparent either when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
196
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(212 citation statements)
references
References 70 publications
(111 reference statements)
12
196
4
Order By: Relevance
“…This object-based correspondence effect has been attributed by many authors to a grasping affordance (the object affordance account; e.g., Iani, Baroni, Pellicano, & Nicoletti, 2011;Pellicano, Iani, Borghi, Rubichi, & Nicoletti, 2010;Tucker & Ellis, 1998). However, other authors have proposed instead that the effect is due primarily, if not entirely, to location coding similar to the coding that underlies the correspondence effects obtained for stimuli displayed in left and right locations (the spatial-coding account; e.g., Bub & Masson, 2010;Cho & Proctor, 2010; see also Bub, Masson, & Lin, 2013). Goslin, Dixon, Fischer, Cangelosi, and Ellis (2012) recently reported a study that they interpreted as providing electrophysiological evidence for the affordance account of such correspondence effects.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…This object-based correspondence effect has been attributed by many authors to a grasping affordance (the object affordance account; e.g., Iani, Baroni, Pellicano, & Nicoletti, 2011;Pellicano, Iani, Borghi, Rubichi, & Nicoletti, 2010;Tucker & Ellis, 1998). However, other authors have proposed instead that the effect is due primarily, if not entirely, to location coding similar to the coding that underlies the correspondence effects obtained for stimuli displayed in left and right locations (the spatial-coding account; e.g., Bub & Masson, 2010;Cho & Proctor, 2010; see also Bub, Masson, & Lin, 2013). Goslin, Dixon, Fischer, Cangelosi, and Ellis (2012) recently reported a study that they interpreted as providing electrophysiological evidence for the affordance account of such correspondence effects.…”
mentioning
confidence: 86%
“…People often respond faster when the orientation of an object's graspable part, irrelevant to the task, corresponds with the response location than when it does not (e.g., Bub & Masson, 2010;Tucker & Ellis, 1998). As a representative example, participants might make a left or right keypress in response to the category of an object with a graspable handle oriented to the left or the right.…”
mentioning
confidence: 99%
“…The abovementioned studies demonstrated a relative presence or absence of activation in motor and perceptual brain areas depending on the context, suggesting that embodied representations are flexible to some degree. These findings emphasize one of the greatest strengths of human language: Words can be used in a flexible manner, that is, depending on the context a word can have different meanings (in a similar vein, Bub & Masson, 2010 showed context-dependent modulations of action priming effects). One way to realize such flexibility in our language system is by assuming that concepts are formed by both contextindependent and context-dependent properties (Barsalou, 1982).…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, while elicitation of affordance effects from observing objects may be bound by the limits of reachable space, objects' names can act as activation cues to stimulus-response compatibility effects for objects within and outside of reachable space (Ferri et al, 2011). Furthermore, studies by Masson, Bub, and Newton-Taylor (2008), Masson, Bub, and Warren (2008), and Bub and Masson (2010) found that the linguistic elicitation of affordances is not limited to single-word processing. In their studies, functional gestures were produced faster after participants had read or listened to sentences referring to objects that afford similar grasps.…”
Section: Visual and Linguistic Cues To Manual Grasp Affordancesmentioning
confidence: 99%